Evolving governance structures in community-based sandfish mariculture and their interactions with livelihood outcomes: Evidence from the Philippines - Fabinyi, Michael; Gorospe, Jay R; McClean, Nicholas; Juinio-Meñez, Marie Antonette (Frontiers in Marine Science, 2022)
Sea cucumber mariculture is an important emerging field of practice and applied research in the coastal tropics. This is due to the existing importance of tropical sea cucumber fisheries for wealth generation and poverty reduction, and the potential for mariculture to contribute to the longer term sustainability of these fisheries while generating benefits additional to those from wild caught sea cucumber. Understanding the optimal institutional arrangements for sea cucumber mariculture is an important area of focus in this field, with a variety of arrangements currently in place. This paper documents the establishment of a communal form of sea ranching in the Philippines, as a case study of community level institutional processes. It describes the background to establishment of the sea ranch in the community of Victory, challenges encountered and how these were managed, and the evolution of governance arrangements. In charting this process, we assess the impacts on livelihood outcomes, highlighting this as a crucial aspect influencing this evolution and the nature of community involvement in the sea ranch. While the sea ranching project generated a range of benefits for livelihoods, including possible spillover effects for the surrounding fishery, substantial economic returns from harvests did not occur. Thus, the system of governing the sea ranch evolved from a communal model to a more exclusive household model primarily to improve operational efficiency. In order for possible benefits of the sea ranch to be sustained and enhanced, greater integration with fisheries management and government support will be needed.